The role of VES-13 to identify limited life expectancy in older adults in primary healthcare settings - Danilo Lopes Assis; Virgínia Oliveira Chagas; Helton Saulo; Claudia Kimie Suemoto; Alfredo Nicodemos Cruz Santana (SciELO, 2021)
ABSTRACT Objective To investigate the potential role of the Vulnerable Elders Survey to identify older adults with limited life expectancy in primary healthcare settings. Method This cross-sectional study was performed in all (nine) healthcare units in Jatai, Goiás (Brazil) from July to December 2018. A sample size of 407 older adults was obtained considering an older population (≥ 60 years old). Participants answered a questionnaire about sociodemographic and clinical characteristics, including the Vulnerable Elders Survey and the Suemoto index. We tested the association between limited life expectancy and the Vulnerable Elders Survey using multiple logistic regression analysis. Results The mean age was 68.9 ± 6.6 yo, and 58.0% were women. The mean score of the Vulnerable Elders Survey was 2.0 ± 2.2, the mean score of Suemoto index was 31.5 ± 21.1%, and 17.2% had limited life expectancy. The Vulnerable Elders Survey was associated with limited life expectancy (OR = 1.57; p = < 0.0001). Conclusion The Vulnerable Elders Survey was able to identify older adults with limited life expectancy in primary healthcare settings and can play a role in detecting older adults who would not benefit from screening and strict control of chronic diseases.